The dragon, the eagle, and the private sector : public-private collaboration in China and the United States - Eggleston, Karen; Donahue, John D.; Zeckhauser, Richard (Cambridge ; New York, NY : Cambridge University Press, 2021)
The governments of China and the United States - despite profound differences in history, culture, economic structure, and political ideology - both engage the private sector in the pursuit of public value. This book employs the term collaborative governance to describe relationships where neither the public nor private party is fully in control, arguing that such shared discretion is needed to deliver value to citizens. This concept is exemplified across a wide range of policy arenas, such as constructing high speed rail, hosting the Olympics, building human capital, and managing the healthcare system. This book will help decision-makers apply the principles of collaborative governance to effectively serve the public, and will enable China and the United States to learn from each other's experiences. It will empower public decision-makers to more wisely engage the private sector. The book's overarching conclusion is that transparency is the key to the legitimate growth of collaborative governance.
Private roles for public goals in China and the United States -- Concepts and context -- Building the railroads that build the nation -- Real estate's intricate tangle of public and private -- A game like no other : delivering the Olympics -- The truest wealth of nations : creating human capital -- Show me where it hurts : state and market in health care -- The transparency imperative.
Title from publisher's bibliographic system (viewed on 08 Feb 2021).
Keywords: Public-private sector cooperation -- China; Public-private sector cooperation -- United States; China -- Economic policy; United States -- Economic policy